Comparison of intrinsic motivation scores for two groups of pre-adolescent athletes - Andress, Jennifer Erin (My University, 2004)
In order for an individual to successfully learn and execute a new movement skill it is expected that they will not only have achieved a specific level of understanding (i.e., cognition), but they will also have had to maintain a level of interest or enthusiasm. The following is a comparison study designed to evaluate the effect of instruction on intrinsic motivation scores. Specifically, the study used a secondary data analysis approach to determine whether an intrinsic motivation score, derived from an attitude based questionnaire differed in a group of minor hockey players who were taught the basic concepts, and allowed to body check versus a group of minor hockey league players that were not permitted to body check. Although the results indicate that there was a significant difference in the intrinsic motivation scores between the two cohorts, the researcher suggests that future studies should consider the many limitations and contributing influences, some of which include team dynamics, game and practice schedules, amount of playing time, method of instruction, as well as the psychological constructs such as self-concept, cognitive maturity, age, and issues of socialization. Further, one may question the importance of cognitive maturity within this cohort since below average cognitive maturity levels may suggest a lack of understanding, especially related to the fundamentals of learning a new movement skill which may in turn influence the individuals motives to perform the skill (i.e., intrinsic motivation).
Keywords: Intrinsic motivation; Sports (Psychological aspects); Athletes (Psychology)